Structural and magnetic characterization of Misajé granitic pluton (NW Cameroon) - (:unkn) unknown (My University, 2016)
The objective of this study was to map the Misajé pluton based on the magnetic susceptibility, petrographic, geochemical and structural (classic) data in order to integrate it in the tectonic evolution of the Central African Fold Belt. It appears at the end of this work that, the Misajé granitic pluton, elongated NNE-SSW is located in the westhern domain of the Pan-African Belt in Cameroon. It was emplaced around 569-560 Ma in the ante-Pan-African basement rocks, composed of biotite hornblende migmatite and amphibolites reactivated in the Pan-African. It (Misajé granitic pluton) consists of biotite hornblende granite, biotite granite, granodiorite and leucocratic granite, differenciated by fractional crystallization.The study area has recorded three deformation phases. The D1 phase, characterized by an E-W foliation in the basement rocks, has been progressively transposed by dominant D2 phase, observed in the basement rocks, biotite hornblende granite and biotite granite. This D2 phase, orientated NE-SW to N-S is dated between 569 ± 12 Ma in the biotite hornblende granite and 560 ± 9 Ma in the biotite granite. The D3, dated at 532 ± 35 Ma is observed in the biotite hornblende orthogneiss. It is characterized by dextral strike-slip with a non-coaxial deformation, which permit (1) the development of the N-S structures and dextral shear movement, (2) the emplacement of leucocratic granite. The microstructural study shows that, in the Misajé pluton, the deformation started during the magmatic state and followed up till the mylonitic state.The rocks of the Misajé granitic pluton are dominated by paramagnetic behavior (54 % of stations). The presence of ferromagnetic minerals reveals that the carriers of the susceptibility are mainly dominated by magnetite that can be euhedral or anhedral. The T Jelinek factor shows that the dominant strain ellipsoids are plano-linear, nevertheless, 80 % of stations have P values less than 1.2, suggesting that, the e
Keywords: African Research